PENANGANAN KEGAWATDARURATAN NYERI AKUT PADA PASIEN FRAKTUR TIBIA DEXTRA TERTUTUP - Pradhita Hendriyeni (Jurnal Ilmiah Cerebral Medika, 2023)
Fractures or fractures are a break in the continuity of bone or cartilage tissue caused by forcedinjuries. According to the World Health Organization (WHO) in 2019 stated that theincidence of fractures is increasing, it was recorded that 20 million people with a prevalencerate of 4.2% experienced fractures due to traffic accidents. The research design used is a casestudy by applying Evidence Based Nursing Practice. The participants in this study were asingle unit, namely Mr.J. This research was conducted on May 19 2023 at the EmergencyRoom of TK III Dr. Reksodiwiryo Padang Hospital. Data collection uses the format ofassessment, interviews, physical examination and documentation. The data analysis stage isby collecting data, presenting data, and concluding. The results of this case study research atthe review stage found that Mr.J was 25 years old. The patient was admitted with a fractureof the tibia dexra due to a traffic accident with a pain scale of 8. Based on the data obtained inthe field, there were three diagnoses that emerged at the time of assessment, namely acutepain b.d biological injury agent (stomach mucosa gastric) d.d complained of pain, lookedgrimacing. Non-pharmacological interventions given to patients to reduce pain intensity arecold compresses. The results of giving cold compresses to patients showed a decrease in thepatient's pain scale.